The Specificity and the Availability of the Folk Lullabies at the Preschool Educational and Upbringing Practice - Ilić, Petar M.; Kovač, Anđelka M.; Pavlović Belojica, Biljana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In this work we show the results of the research aimed at establishing the extent to which educators and parents of the preschool-age kids in Central Serbia and Kosovo and Metohija know the Serbian folk lullabies and use them to send kids to bed. The research results point to the exceptional educational effectiveness and meaning of the folk lullabies but also to their underutilization for both the family-wise and system-wise education and upbringing of the preschool-age kids. We found that the teachers and parents of the preschool-age kids do sometimes sing the traditional folk lullabies while sending kids to bed, can sing a few traditional folk lullabies, and are more aware of the contemporary lullabies instead. We learned that the teachers and the parents of the preschool-age kids do not know the traditional folk lullabies sufficiently enough and therefore do not use them accordingly within the practice, which was the initial hypothesis of the research. The teachers and the parents of the preschool-age kids are interested in learning about the traditional folk lullabies by taking part in the seminars, which would contribute to a greater presence of this type of content within educational and upbringing practice. The conclusion states the necessity for envisioned strategy to promote and familiarise the teachers and the parents with the traditional folk lullabies. There is a need for an instructional booklet containing the selected examples of the folk lullabies, for familiarizing the teachers and the parents with its historical and pedagogical value, and for training them to perform these lullabies. That way they would understand the constructive role the lullabies play at the upbringing, educating, and shaping the national identity.